2000
DOI: 10.1021/ma000216l
|View full text |Cite
|
Sign up to set email alerts
|

Diazosulfonate Polymer Complexes:  Structure and Wettability

Abstract: Polymeric complexes were prepared by using acrylate based copolymers, which contained 20, 30, 50, and 100 mol % diazosulfonate groups and a commercially available fluorinated surfactant (Fluorad FC135). The glass transition temperatures of the complexes were determined to be 71 ± 3 °C, this was independent of the amount of diazogroups. All these complexes are stable up to temperatures of about 200 °C. As determined by wide- and small-angle X-ray diffraction, the solid states of the complexes in the bulk materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…The condensation research on super-hydrophobic surface has important value in practical applications, such as antifrosting in air conditioning and refrigeration, and selfcleaning of car windshield. [3][4][5][6][7][8][9][10][11][12] In these cases, condensate drops are expected to be spherical and depart from the material surface as soon as possible. However, Chen and his partners 13 found that the condensate drops presented either a Cassie state 14 or a mixed Wenzel-Cassie state 15 only on a surface with proper roughness factors.…”
Section: Introductionmentioning
confidence: 99%
“…The condensation research on super-hydrophobic surface has important value in practical applications, such as antifrosting in air conditioning and refrigeration, and selfcleaning of car windshield. [3][4][5][6][7][8][9][10][11][12] In these cases, condensate drops are expected to be spherical and depart from the material surface as soon as possible. However, Chen and his partners 13 found that the condensate drops presented either a Cassie state 14 or a mixed Wenzel-Cassie state 15 only on a surface with proper roughness factors.…”
Section: Introductionmentioning
confidence: 99%
“…Barthlott and Neinhuis , observed the surface microstructure of plant leaves and accounted that the hydrophobic properties were caused by both the surface roughness and wax cover. Zhai et al reported the existence of submicrometer tubular fine structure on micrometric papillae of lotus leaf surface and viewed the hierarchical structure as the main reason for superhydrophobic surface.…”
Section: Introductionmentioning
confidence: 99%
“…Polytetrafluorethylene (PTFE), for example, shows surface tensions of 19 mNm −1 ; to achieve lower surface tensions, interfaces must be generated that are enriched with more CF 3 groups than for PTFE. Thünemann reported strategies for preparing polyelectrolyte‐surfactant complexes with fluorinated surfactants on the basis of self‐organization to create surfaces with surface tensions down to 6 mNm −1 ,1–4 but this concept is limited to polyelectrolytes.…”
Section: Introductionmentioning
confidence: 99%